Childhood Guillain–Barre syndrome in the SARS‐CoV‐2 era: Is there any causative relation?. Issue 12 (20th December 2022) - Pourbakhtyaran, Elham; Heidari, Morteza; Akbari, Masood Ghahvechi; Mohammadi, Mahmoud; Badv, Reza Shervin; Zamani, Gholamreza; Tavasoli, Ali Reza; Rezaei, Zahra; Mamishi, Setareh; Haji Esmaeil Memar, Elmira; Hosseiny, Seyyed Mohammad Mahdi; Ghabeli, Homa; et al.
Abstract: We reported an association between SARS‐CoV‐2 infection and Guillain–Barre syndrome (GBS). From 37 patients with GBS, previous SARS‐CoV‐2 clinical clues, including fever, cough, and diarrhea, were recorded in 18 patients. Among them, SARS‐CoV‐2 IgG was detected in seven patients, considered confirmed as cases. SARS‐CoV‐2 PCR was positive in just one patient. Although we found no increase in patient recruitment during the pandemic compared to previous years, our study indicated that SARS‐CoV‐2 is associated with poorer outcomes regarding GBS disability scale and hospital stay. Abstract : Although the rate of Guillain–Barre syndrome in children associated with SARS‐CoV‐2 was the same as previous years, it would be related to more hospital stay and serious complications that is necessary for pediatric neurologists to mention.